2019
DOI: 10.1093/tropej/fmy078
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Tpeak-Tend Interval and QTdis, and Pdis in Children with Brucellosis

Abstract: Objective To investigate the effect of inflammation on the conducting system of the heart in patients diagnosed with brucellosis. Methods A total of 42 patients diagnosed with brucellosis and 39 age and sex-matched healthy children were enrolled into the study. Pre- and post-treatment electrocardiographic parameters in brucellosis and control group were recorded from an electrocardiogram for each patient. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Fever and monoarthritis, often involving the hip and/or knee joint are common clinical findings in brucellosis; however, no disease-specific pathognomonic signs and symptoms exist [5][6][7]. Although rarely, brucellosis can be associated with a variety of clinical findings; including acute renal failure, endocarditis, splenic abscess, spondylitis, and encephalitis [4,[8][9]. Laboratory tests can often yield normal inflammatory biomarker levels [5].…”
Section: Introductionmentioning
confidence: 99%
“…Fever and monoarthritis, often involving the hip and/or knee joint are common clinical findings in brucellosis; however, no disease-specific pathognomonic signs and symptoms exist [5][6][7]. Although rarely, brucellosis can be associated with a variety of clinical findings; including acute renal failure, endocarditis, splenic abscess, spondylitis, and encephalitis [4,[8][9]. Laboratory tests can often yield normal inflammatory biomarker levels [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that some microorganisms such as Chlamydia pneumoniae and Human cytomegalovirus can cause endothelial dysfunction by affecting the artery walls [ 21 ]. Cetin et al [ 22 ] in their study on pediatric patients with brucella infection reported that there was more heart involvement than expected and that this could be more like subclinical heart involvement. We hypothesized the study to evaluate the role of IMA, gal-3, PON-1, and MPO biomarkers, which are used in the evaluation of the etiopathogenesis of atherosclerosis in patients with acute brucellosis infection, in the pathophysiology of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Brucella endocarditis has a predominance of aortic involvement and is prone to left ventricular failure ( 12 ). Cetin M et al demonstrated that the parameters of ECG including Pmax, Pdis, QTmax, QTdis, QTcdis, Tp-edis interval, Tp-emax/QTmax, and Tp-emax/QTcmax ratios were significantly longer among children with brucellosis compared with healthy children, which indicates that the cardiac conduction pathways are affected ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have described and considered the potential mechanisms of a case of brucellosis with relative bradycardia. Relative bradycardia could be used as a clinical tool for the diagnosis of various disease etiologies, especially infectious diseases ( 4 , 13 ). Our case demonstrates that relative bradycardia could be associated with B. melitensis infection, an observation that has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%